A miniaturized tri-band bandpass microstrip filter using multiple resonators with sharp skirts. Issue 5 (24th June 2021) - Wang, Chenhao; Xi, Xiaoli; Zhao, Yuchen; Shi, Xiaomin
Abstract: In this paper, a miniaturized tri-band bandpass microstrip filter using stub loaded rectangular ring resonator (SLRRR)，shorted stub loaded stepped impedance resonators (SSLSIR), and stepped impedance resonators (SIR) with sharp skirts is presented. Two SSLSIRs are embedded paralleled inside SLRRR to generate a quasi-elliptic response at second and third passband. The odd-even fundamental resonant mode and first high-order resonant mode of the SIRs are exploited to generate tri-band response. Three bandwidths can be controlled independently due to different signal paths. Extra transmission zeros are introduced by the configuration of 0° feed structure. Sharp skirts are achieved at the upper edge of each passband by λg /4 lines which are loaded at the I/O ports. An example of the proposed tri-band filter operating at 2.76 GHz/5.7 GHz/7.63 GHz for TDD-LTE/WLAN/VSAT applications is implemented and fabricated. The simulation and measurement show a good agreement.